Effect of Folic Acid Supplementation for Reducing Methotrexate Side Effects in Patients with Rheumatoid Arthritis: an Evidence-based Case Report - Athira Presialia; Bambang Setyohadi (Indonesian Journal of Rheumatology, 2020)
Background: Rheumatoid arthritis is a chronic inflammatory joint disease,indicated by a symmetrical erosive synovitis. Disease-modifying anti-rheumaticdrugs (DMARDs) are known to interfere with signs and symptoms of RA, improvephysical function and therefore increase patient productivity. Methotrexate is ananchor drug for rheumatoid arthritis patients, however, its related mechanism ofaction with folate deficiency resulting in some side effects, includinggastrointestinal and liver toxicity. Folic acid supplementation may reduce theseside effects. Method: A search was conducted on Pubmed, Cochrane, EBSCOhost,and ProQuest. After the selection of title and abstract was done using inclusionand exclusion criteria, which led to one relevant article. The selected study wascritically appraised for its validity, importance, and applicability. Result: Inrheumatoid arthritis patient receiving methotrexate, there was a statisticallysignificant reduction in the incidence of abnormal transaminase elevation (RR:0.19, 95% CI: 0.10-0.36), but the reduction in gastrointestinal side effects did notreach statistical significance (RR: 0.76, 95% CI: 0.57-1.01) Conclusion: Folic acidsupplementation has an effect in reducing gastrointestinal and liver toxicity as sideeffects of methotrexate in rheumatoid arthritis patients.